2013
DOI: 10.1021/jm4003457
|View full text |Cite
|
Sign up to set email alerts
|

Development of Flavonoid-Based Inverse Agonists of the Key Signaling Receptor US28 of Human Cytomegalovirus

Abstract: A series of 31 chalcone- and flavonoid-based derivatives were synthesized in good overall yields and screened for their inverse agonist activity on the US28 receptor of human cytomegalovirus (HCMV). With one exception (e.g., 2-(5-bromo-2-methoxyphenyl)-3-hydroxy-4H-chromen-4-one), halogen-substituted flavonoids were typically more potent inverse agonists than their related hydro derivatives. While toxicity could be used to partially explain the inverse agonist activity of some members of the series, 5-(benzylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…However, we did not observed any apparent inhibitory effect of the flavonoid on viral adsorption to HEp-2 cells. It was also reported that flavonoid from Ocotea notata leaves have been shown to exhibit extracellular virus-inactivating activity, as observed in the present study (Kralj et al, 2013). HSV enters cells by fusion with plasma membranes through a process carried out by the sequential activity of envelope glycoproteins, including gB and gD, etc.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, we did not observed any apparent inhibitory effect of the flavonoid on viral adsorption to HEp-2 cells. It was also reported that flavonoid from Ocotea notata leaves have been shown to exhibit extracellular virus-inactivating activity, as observed in the present study (Kralj et al, 2013). HSV enters cells by fusion with plasma membranes through a process carried out by the sequential activity of envelope glycoproteins, including gB and gD, etc.…”
Section: Discussionsupporting
confidence: 83%
“…Many pharmacological properties of flavonoids, especially antiviral actions have been reported in the scientific literature (Hayashi et al, 2012;Nijveldt et al, 2001). Studies have demonstrated that the flavonoids extracted from herbs in addition to different properties like anti-allergic, inflammatory, microbial and cancer activity, they also exert antiviral activities against a wide spectrum of vicious human pathogens, including human immunodeficiency virus type 1, herpes simplex virus, vesicular stomatitis virus and human cytomegalovirus (Cefarelli et al, 2006;Kralj et al, 2013;li et al, 2000;Middleton et al, 2000). These findings are crucial for understanding the pharmacological properties of flavonoids which, despite extensive studies of different flavonoid antiviral properties derived from P. perfoliatum l., are still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Di- and tetra-hydro-isoquinolines were identified as promising lead structures as allosteric inverse agonists of US28 and several derivatives have been shown to reduce US28 signaling [106]. Recently, flavonoid-based compounds were shown to inhibit US28 as inverse agonists [107]. A recent study suggests that some inverse agonists of US28 desensitize its downstream signaling via constitutive endocytosis of US28.…”
Section: Hcmv Us28mentioning
confidence: 99%
“…US28 was reported to activate ERK1/2 in an agonist-dependent manner, engaging the G proteins Gα i1 and Gα 16 , in response to RANTES/CCL5 [25]. As described before, also an agonist-independent downstream activation of ERK1/2 can be observed in US28-expressing HEK293T cells [56]. With use of the MEK1/2 inhibitor PD184352 and the ERK1/2 inhibitor FR180204 we intended to suppress US28-mediated ERK1/2 activation and thus reduction of CXCR4 surface expression.…”
Section: Discussionmentioning
confidence: 90%